2018
DOI: 10.1021/jacs.7b11132
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Silylation of N2 and Synthesis of NH3 and N2H4 by Net Hydrogen Atom Transfer Reactions Using a Chromium P4 Macrocycle

Abstract: We report the first discrete molecular Cr-based catalysts for the reduction of N. This study is focused on the reactivity of the Cr-N complex, trans-[Cr(N)(PN)] (PCr(N)), bearing a 16-membered tetraphosphine macrocycle. The architecture of the [16]-PN ligand is critical to preserve the structural integrity of the catalyst. PCr(N) was found to mediate the reduction of N at room temperature and 1 atm pressure by three complementary reaction pathways: (1) Cr-catalyzed reduction of N to N(SiMe) by Na and MeSiCl, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 93 publications
1
49
0
Order By: Relevance
“…Desorption of second NH 3 molecule from the substrate can be facilitated by protonation of NH 3 to NH 4 + , which is −0.13 eV downhill in the energy profile (Figure ), and NH 4 + ion obtained as the reduced product can be easily harvested using a suitable counterion. This is concordant with previous experimental reports as they also found NH 4 + and N 2 H 5 + as the reduced product of N 2 …”
Section: Resultssupporting
confidence: 94%
“…Desorption of second NH 3 molecule from the substrate can be facilitated by protonation of NH 3 to NH 4 + , which is −0.13 eV downhill in the energy profile (Figure ), and NH 4 + ion obtained as the reduced product can be easily harvested using a suitable counterion. This is concordant with previous experimental reports as they also found NH 4 + and N 2 H 5 + as the reduced product of N 2 …”
Section: Resultssupporting
confidence: 94%
“…While Cr dinitrogen complexes bearing diphosphine [123] and triphosphine [98] ligands [Cr(N 2 ) 2 (P Bn 2 N Ph 2 ) 2 ] ( 128 ) and [Cr(N 2 )(P Bn 3 N Ph 3 )] ( 129 ) with pendant amines were not reported to mediate N 2 protonation (Scheme 25 a), the macrocyclic P 4 N 4 chromium complex [Cr(N 2 )(P Bn 4 N Ph 4 )] ( 130 ) generates a mixture of N 2 H 5 + and NH 4 + , in presence of excess acid and reducing agent. The ratio between the two products being dependent of the reaction conditions: hydrazine is favored at low temperature while ammonia is obtained in quantitative yield at room temperature [124, 125] . DFT calculations suggested that upon protonation, 130 generates the diazenido complex [Cr(N=NH)(P Bn 4 N Ph 4 )] + ( 131 ), together with the hydride complex [CrH(N 2 )(P Bn 4 N Ph 4 )] + ( 132 ) (Scheme 25 b, inset) [124] .…”
Section: Associative Pathwaysmentioning
confidence: 99%
“…Most importantly, this complex was used to illustrate the first functionalization by hydrogen atom transfer of an end‐on bound dinitrogen ligand: NH 3 was quantitively obtained from the reaction of 130 with TEMPOH (2,2,6,6‐tetramethylpiperidine‐1‐ol) (Scheme 25 b). [125] …”
Section: Associative Pathwaysmentioning
confidence: 99%
“…Conversely, reactions with hydroboranes and ‐silanes either lead to 1,2‐/1,3‐addition products [6, 7] or boryl/silyl amines (Scheme 1 a/b), [6d,i] driven by the hydridic character of the B/Si−H bonds and formation of strong N−B and N−Si bonds in the products. In fact, N−Si bond formation has become a popular strategy for converting dinitrogen into ammonia equivalents [7h,i] . With respect to metal‐free activation of N 2 , our group has shown that carbene‐stabilized borylenes are capable of capturing and reducing N 2 , [8] while Stephan and co‐workers recently established that sterically encumbered diazomethanes can undergo 1,1‐hydroboration at the terminal N atom with Pier's borane (HB(C 6 F 5 ) 2 ) and form a stable diazomethane‐borane adduct with B(C 6 F 5 ) 3 [9] …”
Section: Introductionmentioning
confidence: 99%